2019
DOI: 10.1101/537464
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Multiple human adipocyte subtypes and mechanisms of their development”

Abstract: Human adipose tissue depots perform numerous diverse physiological functions, and are differentially linked to metabolic disease risk, yet only two major human adipocyte subtypes have been described, white and "brown/brite/beige." The diversity and lineages of adipocyte classes have been studied in mice using genetic methods that cannot be applied in humans. Here we circumvent this problem by studying the fate of single mesenchymal progenitor cells obtained from human adipose tissue. We report that a minimum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…2b). This finding aligns with previous studies associating TRHDE-AS1 with human adipocyte tissue development 27 . However, our analysis also reveals three lncRNAs, namely LINC01060 , RP11-231C18.3 , and RP11-1017G21.4 , which exhibited significantly high specificity scores in basal cells, NKT (natural killer T) cells, and mucosal cells, respectively.…”
Section: Resultssupporting
confidence: 93%
“…2b). This finding aligns with previous studies associating TRHDE-AS1 with human adipocyte tissue development 27 . However, our analysis also reveals three lncRNAs, namely LINC01060 , RP11-231C18.3 , and RP11-1017G21.4 , which exhibited significantly high specificity scores in basal cells, NKT (natural killer T) cells, and mucosal cells, respectively.…”
Section: Resultssupporting
confidence: 93%
“…One would hypothesize that decreased adipose tissue mass in ARC −/− mice would have resulted in improved insulin sensitivity and glucose tolerance, but we did not observe such improvements in this study. Although studies have shown that ARC is expressed in white and brown adipose tissue depots (Rosell et al 2014, Liu et al 2015, Min et al 2019, relatively little is known about the role of ARC in adipose tissue. Thus, it is possible that loss of ARC in adipose tissue impacts glucose homeostasis.…”
Section: Journal Of Endocrinologymentioning
confidence: 99%